The role of strategy implementation practices on performance of the public sector organisations - Pachalo M. Mwanza; Javaid A. Dar (Africa’s Public Service Delivery & Performance Review)
Background: Effective strategy implementation is crucial for public sector organisations. Despite the importance of strategic planning, many public organisations struggle with execution, leading to performance gaps. This study addresses the limited research on strategy implementation in public companies.